THE US STRATEGY FOR SHORT-TERM MILITARY ARTIFICIAL INTELLIGENCE DEVELOPMENT (2020-2030) - Barreiros, Daniel; Poty, Ítalo Barreto (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article analyses the US Department of Defense initiative formalized in the Summary of the 2018 Department of Defense Artificial Intelligence Strategy. The conclusion is that the US emphasis on the use of artificial intelligence to expand C4ISR capabilities (command, control, communications, computers, intelligence, reconnaissance and surveillance) and the denunciation of “ethical risks’’ involving Lethal Autonomous Weapon Systems (LAWS) are narrative strategies aimed at dealing in the short term with the inability of the US technology agencies to master autonomous military platform technologies and with the Russian resolve on the development of these lethal autonomous military platforms.